Chương trình đảm bảo chất lượng cho thiết bị xạ trị ung thư vú trong mổ - intrabeam - Thành, Nguyễn Văn; Hùng, Lê Trọng; Tuấn, Nguyễn Hữu Minh; Dũng, Nguyễn Cao; Sơn, Hoàng Đình Nguyễn; Khoa, Nguyễn Đắc; Lanh, Nguyễn Văn; Cường, Nguyễn Mạnh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
AA